The effect of Western TV on crime: Evidence form East Germany - Tim Friehe; Helge Müller; Florian Neumeier (Philipps-University Marburg, School of Business and Economics, 2017)
This paper explores the causal influence of Western television programming on crime rates. We exploit a natural experiment involving access to West German TV within the German Democratic Republic (GDR) in which only geography and topography determined the allocation of individuals to treatment and control groups. Focusing on violent and property crime (as these domains were most likely to be affected by the marked differences in TV content), we find that in the post-reunification decade in which TV content was harmonized, regions that had access to Western TV broadcasts prior to the reunification experienced lower rates of violent crime, sex crime, and theft, but more fraud.
Keywords: J22; K42; P37; P39; 330; Television; Media; Natural experiment; Germany